A 200 km-long mercury contamination of the Paglia and Tiber floodplain: Monitoring results and implications for environmental management. (December 2019) - Rimondi, V.; Costagliola, P.; Lattanzi, P.; Morelli, G.; Cara, G.; Cencetti, C.; Fagotti, C.; Fredduzzi, A.; Marchetti, G.; Sconocchia, A.; Torricelli, S.
Abstract: This paper reports the results of a joint project carried out by three regional environmental agencies of Italy to evaluate long-range mercury (Hg) transport from the abandoned Mt. Amiata Hg district in southern Tuscany (the third largest worldwide site for Hg production) to the fluvial ecosystems of the Paglia and Tiber rivers. Most of the work focused on stream sediments, surface waters and soils. A preliminary survey of Hg 0 content in air was also conducted. Data obtained by public health authorities on Hg in vegetables and fish were also included. The highest Hg concentrations (up to thousands of μg/g Hg) were observed in stream sediments and soils directly impacted by Hg mine runoff. Although progressive Hg dilution was observed from north to south along the river, sediments and soils show anomalous Hg levels for over 200 km downstream of Mt. Amiata, testifying to an extreme case of long-range Hg contamination. A pervasive redistribution of Hg is observed in all sediment compartments. Presumably, the width of the impacted fluvial corridor corresponds to the entire alluvial plains of the rivers. The floodplains can be considered new sources for downstream Hg redistribution, especially during large flood events. On the other hand, results from water, air, and vegetable sampling indicate low potential for human exposure to Hg. The extent and distribution of the contamination make remediation not viable. Therefore, people and human activities must coexist with such an anomaly. On the technical side, the most urgent action to be taken is a better definition of the exact extent of the contaminated area. On the management side, it is necessary to identify which public institution(s) can best deal with such a widespread phenomenon. According to the precautionary principle, the impact of the contamination on human activities in the affected areas should be considered. Graphical abstract: Image 1 Highlights: Mercury transport on the Tiber River (Italy) and related sub-basins was investigated. A yearlong joint study was conducted by the three Environmental Agencies. Longitudinally contamination of sediment extends over 200 km, up to the Tyrrhenian Sea. The width of the impacted fluvial corridor likely corresponds to the entire alluvial plains. Human exposure (air, fish, edible vegetables) to mercury is low. Abstract : One of the most extreme cases of long-range heavy metal (mercury) contamination of fluvial sediments due to past mining activity ever reported in literature.